Insulin-Induced NF-κB Activation May Contribute to Doxorubicin Resistance in Luminal A T-47D Breast Cancer Cells - Wibisono Hasanul Muhtaram; Novrita Padauleng; Rizka Vidya Lestari (Faculty of Medicine, Universitas Mataram, 2026)
Doxorubicin is an effective chemotherapy agent for breast cancer; however, its efficacy is often limited by cellular resistance. Insulin is hypothesized to enhance anti-apoptotic activity through activation of Nuclear Factor Kappa-Beta (NF-κB), although its mechanism in the Luminal A subtype T-47D cell line has not been extensively studied. This analytical experimental study with a post-test only paired design used T-47D cells divided into insulin-treated and non-insulin groups. Both groups were exposed to various concentrations of doxorubicin, namely 0 (control), 3.125, 6.25, 12.5, 25, 50, and 100 µg/mL. NF-κB activation was measured as pNF-κB concentration using the ELISA method. Data were analyzed using the Shapiro–Wilk test for normality followed by a paired t-test. The insulin-treated group showed higher mean pNF-κB concentrations compared to the non-insulin group across all doxorubicin doses. Significant differences were observed at 0 µg/mL (p = 0.008), 3.125 µg/mL (p = 0.009), and 100 µg/mL (p = 0.045), whereas no significant differences were found at concentrations between 6.25 and 50 µg/mL (p > 0.05). Overall, increasing doxorubicin concentrations reduced pNF-κB levels; however, insulin treatment maintained higher pNF-κB levels compared to the non-insulin group. These findings indicate that insulin increases NF-κB activation in doxorubicin-treated T-47D breast cancer cells and may sustain NF-κB activity against the cytotoxic effects of doxorubicin.